Identifying Patterns in Financial Markets New Approach Combining Rules Between PIPs and SAX - Leitão, João.; Neves, Rui Ferreira; Horta, Nuno C.G.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book describes a new pattern discovery approach based on the combination among rules between Perceptually Important Points (PIPs) and the Symbolic Aggregate approximation (SAX) representation optimized by Genetic Algorithm (GA). The proposed approach was tested with real data from S&P500 index and all the results obtained outperform the Buy&Hold strategy. Three different case studies are presented by the authors.
Introduction -- Related Work -- SIR/GA approach -- Case studies.
Keywords: Computational intelligence; Algorithms; Social sciences -- Mathematics; Pattern recognition systems; Computational Intelligence; Algorithms; Mathematics in Business, Economics and Finance; Automated Pattern Recognition